Mössbauer Spectroscopic Analysis of La1−xSrxFeO3−δ Perovskites. Issue 4 (8th February 2023) - Lu, Zeyi; Shen, Jiyu; Zou, Jiangqiang; Zhang, Qinghang; Mo, Jiajun; Wu, Zhongjin; Xia, Yanfang; Liu, Min
Abstract : Herein, the effects of different Sr content doping on the crystal structure and electronic structure of La1− x Sr x FeO3− δ (LSFO‐ x, x  = 0, 0.2, 0.5, 0.8, 1.0) are studied by X‐ray diffraction (XRD) and Mössbauer spectroscopy. It is shown in the XRD results that the structure of LSFO‐ x changes from orthorhombic (Pnma [#62]) to cubic (Pm‐3m (#221)) to tetragonal (I4/mmm (#139)) with increasing strontium doping. It is shown in Mössbauer spectrum analysis that with the gradual increase of Sr doping, iron ions finally change from +3 oxidation state to +4 oxidation state after passing through an intermediate oxidation state of +3.5. The Fe 3.5+ state can result from rapid electron exchange (Fe 3+  + Fe 4+  ⇋ Fe 4+  + Fe 3+ ) between iron ions of different oxidation states within the crystal structure; the study provides some reference for future research to study the effect of iron‐oxidation state on the specific activity of strontium‐doped LaFeO3 . Abstract : Herein, the effects of different Sr content doping on the crystal structure and electronic structure of La1− x Sr x FeO3− δ ( x  = 0, 0.2, 0.5, 0.8, 1.0) are studied by X‐ray diffraction (XRD) and Mössbauer spectroscopy. The study provides some reference for future research to study the effect of iron‐oxidation state on the specific activity of strontium‐doped LaFeO3 .